Pole piece and preparation method thereof, battery and electric equipment
By using cellulose ether polymers in the active material layer of the electrode sheet, the energy density loss and pore structure integrity problems in the electrode sheet porosity regulation are solved, and efficient electrolyte infiltration and battery performance improvement are achieved.
Patent Information
- Application Number
- CN202411703628.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-11-25
AI Technical Summary
When adjusting the porosity of the porosity, the prior art can easily lead to energy density loss, uneven pore distribution and poor pore structure integrity, and mechanical needle hole-making methods may damage the porosity.
Cellulose ether polymers are used to form pores in situ in the active material layer. By spraying the cellulose ether polymer solution and drying, uniform and rich pores are formed, thereby improving the porosity of the electrode sheet and the electrolyte wetting property.
Without changing the electrode plate design and not causing mechanical damage to the electrode plate, the porosity and electrolyte wetting properties of the electrode plate are significantly improved, and the high-rate performance, energy density, cycle stability and safety of the battery are improved.
Smart Images

Figure CN119812327A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and specifically relates to a pole piece and a preparation method thereof, a battery and an electrical device. Background Art
[0002] The infiltration of the electrolyte into the electrode and the electrical properties such as the long cycle of the battery cell are greatly affected by the porosity of the electrode. The current conventional practice is to adjust the overall porosity of the electrode by adjusting the surface density and compaction density of the electrode. However, high porosity is mainly achieved through a lower compaction density, which results in a loss of energy density and problems such as uneven pore distribution and poor integrity of the pore structure. Another approach is to create holes by mechanical needle puncture. The advantage is that the size and distribution of the holes are uniform and controllable, but the disadvantage is that it is easy to damage the electrode, and the squeezed dressing may also fall or accumulate at the edge of the hole, thereby affecting the uniformity of the electrode plane, and in severe cases may cause interface problems. Summary of the invention
[0003] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the purpose of the present application is to propose a pole piece and a method for preparing the same, a battery and an electrical device. The cellulose ether polymer in the active material layer of the present application can form pores in situ in the active material layer, and effectively improve the porosity and electrolyte wettability of the pole piece without changing the pole piece design or causing mechanical damage to the pole piece. Moreover, after the pole piece is infiltrated with the electrolyte, the cellulose ether polymer can be transformed into a gel state, which can improve the wettability of the electrolyte to the pole piece and the liquid retention rate of the pole piece. In addition, the cellulose ether polymer in the pole piece will consume a trace amount of water when infiltrated in the electrolyte, and initiate a reactive grafting reaction on its side chain, which can not only effectively improve the affinity and ion conductivity of the electrolyte, but also inhibit the side reactions caused by water.
[0004] In one aspect of the present application, the present application provides a pole piece. According to an embodiment of the present application, the pole piece includes:
[0005] current collector;
[0006] An active material layer is disposed on at least a portion of the surface of the current collector, and the active material layer includes a cellulose ether polymer, and the cellulose ether polymer is located in the gaps contained in the active material layer.
[0007] According to the pole piece of the embodiment of the present application, the active material layer includes cellulose ether polymers, and the cellulose ether polymers can form pores in situ in the active material layer. In this way, the porosity of the pole piece can be effectively improved without changing the pole piece design or causing mechanical damage to the pole piece. At the same time, the created pores have the advantages of uniform distribution and good pore structure integrity. The uniform and abundant pores can significantly improve the wettability of the electrolyte. Moreover, after the pole piece is infiltrated with the electrolyte, the cellulose ether polymers in the active material layer can be transformed into a gel state, which limits the fluidity of the electrolyte, and can further improve the wettability of the electrolyte to the pole piece and the liquid retention rate of the pole piece. In addition, the cellulose ether polymers in the pole piece will consume a small amount of water when infiltrated in the electrolyte, and initiate a grafting reaction on its side chain, which can not only effectively improve the affinity and ion conductivity of the electrolyte, but also act as a moisture absorbent to capture the residual moisture in the battery cell after baking, and inhibit the side reactions caused by moisture.
[0008] In addition, the pole piece according to the above embodiment of the present application may also have the following additional technical features:
[0009] In some embodiments of the present application, the weight average molecular weight of the cellulose ether polymer is 20,000-200,000.
[0010] In some embodiments of the present application, the cellulose ether polymer includes at least one of hydroxypropyl methylcellulose, hydroxyethyl methylcellulose and hydroxypropyl ethylcellulose.
[0011] In some embodiments of the present application, the mass proportion of the cellulose ether polymer in the active material layer is 1% to 5%.
[0012] In some embodiments of the present application, the electrode sheet is a positive electrode sheet, and the porosity of the positive electrode sheet is 36.5% to 40%.
[0013] In some embodiments of the present application, the electrode sheet is a negative electrode sheet, and the porosity of the negative electrode sheet is 38.5% to 42%.
[0014] In a second aspect of the present application, the present application proposes a method for preparing the pole piece of the first aspect. According to an embodiment of the present application, the method comprises:
[0015] A cellulose ether polymer solution is formed on at least a portion of the surface of the active material layer away from the current collector, and dried to obtain a pole piece.
[0016] According to the method for preparing the pole piece of the embodiment of the present application, a cellulose ether polymer solution is sprayed into the coated pole piece. After drying, the cellulose ether polymer solution evaporates, the cellulose ether polymer matrix shrinks, and pores are formed in situ. The method of the present application is simple, and the porosity of the pole piece is effectively improved without changing the pole piece design or damaging the pole piece. At the same time, the created pores have the advantages of uniform distribution and good pore structure integrity. The uniform and abundant pores can significantly improve the wettability of the electrolyte. The rapidly shrunk sprayed cellulose ether polymer can also slowly absorb a large amount of electrolyte and gel, which can limit the fluidity of the electrolyte and effectively improve the liquid retention capacity of the pole piece. In addition, the cellulose ether polymer in the pole piece will consume a small amount of water when it is soaked in the electrolyte, and initiate a grafting reaction on its side chain, which can not only effectively improve the affinity and ion conductivity of the electrolyte, but also act as a moisture absorbent to capture the residual moisture in the battery cell after baking and inhibit the side reactions caused by moisture.
[0017] In addition, the method according to the above embodiment of the present application may also have the following additional technical features:
[0018] In some embodiments of the present application, the mass concentration of the cellulose ether polymer solution is 0.5 wt % to 15 wt %.
[0019] In some embodiments of the present application, the viscosity of the cellulose ether polymer solution is 200 mPa.s to 1500 mPa.s.
[0020] In some embodiments of the present application, the solvent in the cellulose ether polymer solution includes at least one of N,N-dimethylformamide, N-methylpyrrolidone and dimethyl sulfoxide.
[0021] In some embodiments of the present application, the cellulose ether polymer solution is sprayed in an atomized manner on at least a portion of the surface of the active material layer away from the current collector, and dried to obtain a pole piece.
[0022] In the third aspect of the present application, the present application proposes a battery. According to an embodiment of the present application, the battery has a pole piece of the above embodiment or a pole piece made by the method of the above embodiment. Thus, the high rate performance, energy density, cycle stability and safety of the battery can be effectively improved.
[0023] In the fourth aspect of the present application, the present application proposes an electric device. According to an embodiment of the present application, the electric device has the battery as described above. Therefore, the electric device has all the advantages of the battery, which will not be described in detail here.
[0024] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0026] Figure 1 A schematic diagram of the process of preparing a pole piece in some embodiments of the present application;
[0027] Figure 2 A schematic diagram of hole making in the positive electrode sheet of some embodiments of the present application;
[0028] Figure 3 Schematic diagram of hole making in the negative electrode sheet of some embodiments of the present application.
[0029] The attached drawings are marked as follows: 201 - positive electrode active material layer dressing, 202 - positive electrode polymer droplets, 203 - polymer layer shrunk after drying, 204 - pores left after polymer shrinkage, 301 - negative electrode active material layer dressing, 302 - negative electrode polymer droplets, 303 - polymer skeleton after phase transfer, 304 - polymer particles after drying, 305 - polymer skeleton after drying, 306 - finger-like pores. DETAILED DESCRIPTION
[0030] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limiting the present application.
[0031] In one aspect of the present application, the present application proposes a pole piece. According to an embodiment of the present application, the pole piece includes: a current collector; an active material layer, the active material layer is disposed on at least a portion of the surface of the current collector, the active material layer includes a cellulose ether polymer, and the cellulose ether polymer is located in the gaps contained in the active material layer.
[0032] The beneficial effects that can be achieved by the pole piece proposed in this application are described in detail below:
[0033] The active material layer of the present application includes cellulose ether polymers, which can form pores in situ in the active material layer. In this way, the porosity of the electrode can be effectively improved without changing the electrode design or causing mechanical damage to the electrode. At the same time, the created pores have the advantages of uniform distribution and good pore structure integrity. The uniform and abundant pores can significantly improve the wettability of the electrolyte. Moreover, after the electrode is infiltrated with the electrolyte, the cellulose ether polymer in the active material layer can be transformed into a gel state, which limits the fluidity of the electrolyte, and can further improve the wettability of the electrolyte to the electrode and the liquid retention rate of the electrode.
[0034] In addition, when LiPF6 and trace water exist in the electrolyte at the same time, the side chains of cellulose ether polymers can also be grafted with the ring-opening polymerization products of ethylene carbonate (EC) in the electrolyte through ester exchange under the action of trace water, which can effectively improve the affinity and ion conductivity of the electrolyte; at the same time, a small amount of water will be consumed during the reaction, which can effectively remove trace moisture in the electrode or electrolyte in the battery cell and effectively inhibit the occurrence of side reactions.
[0035] However, artificial synthetic polymers such as polyacrylonitrile, polymethyl methacrylate, and polyethylene oxide cannot achieve the technical effect of the present application. Such polymers are limited by their high crystallinity and preparation methods, have low porosity, and have limited plasticizing effects on electrolytes. They also have poor absorption of electrolytes (generally 100wt% to 300wt%) and poor affinity for electrolytes.
[0036] According to some specific embodiments of the present application, the weight average molecular weight of the cellulose ether polymer is 20,000 to 200,000, for example, 20,000, 60,000, 80,000, 100,000, 120,000, 140,000, 160,000, 180,000, 200,000, etc. By limiting the weight average molecular weight of the cellulose ether polymer to the above range, it is possible to further ensure that the cellulose ether polymer forms effective pores in situ in the active material layer, and at the same time ensure that the cellulose ether polymer has a high liquid absorption rate. For example, when the weight average molecular weight of the cellulose ether polymer is 200,000, its liquid absorption rate is about 1700 wt%.
[0037] According to some further specific embodiments of the present application, the cellulose ether polymer includes at least one of hydroxypropyl methylcellulose, hydroxyethyl methylcellulose and hydroxypropyl ethyl cellulose, so that the above-mentioned types of cellulose ether polymers can form pores in situ in the active material layer, and the pores formed have the advantages of uniform distribution and good pore structure integrity, and after the electrode is infiltrated with the electrolyte, the above-mentioned types of cellulose ether polymers can be transformed into a gel state, which can further improve the wettability of the electrolyte to the electrode and further improve the liquid retention rate of the electrode. In addition, the above-mentioned types of cellulose ether polymers are low-cost, green and environmentally friendly, and have an ultra-high liquid absorption rate.
[0038] According to some other specific embodiments of the present application, the mass proportion of cellulose ether polymers in the active material layer is 1% to 5%, for example, it can be 1%, 2%, 3%, 4%, 5%, etc. By limiting the mass proportion of cellulose ether polymers in the active material layer to the above range, the porosity of the electrode can be further improved, the wettability of the electrolyte to the electrode can be further improved, and the liquid retention rate of the electrode can be further improved.
[0039] The technical solution of the present application is applicable not only to positive electrode sheets, but also to negative electrode sheets. In the positive electrode sheets, the cellulose ether polymers that shrink at the edges of the gaps have a certain supporting effect, which protects the integrity of the pore structure to a certain extent. In the negative electrode sheets, the cellulose ether polymers themselves have a good structural retention effect, the molecular chains are relatively stretched, and they have more electrolyte contact and reaction sites, which effectively improves the efficiency of electrolyte infiltration; at the same time, the internal wrinkles and pores produced by the swelling of the cellulose ether polymers when absorbing the electrolyte can absorb and store a large amount of electrolyte, which further improves the infiltration and liquid retention capacity of the negative electrode sheets.
[0040] According to some specific embodiments of the present application, the electrode sheet is a positive electrode sheet, and the porosity of the positive electrode sheet is 36.5% to 40%, for example, it can be 36.5%, 37%, 37.5%, 38%, 38.5%, 39%, 39.5%, 40%, etc., thereby further improving the wettability of the electrolyte to the positive electrode sheet and further improving the liquid retention rate of the positive electrode sheet.
[0041] According to some further specific embodiments of the present application, the electrode sheet is a negative electrode sheet, and the porosity of the negative electrode sheet is 38.5% to 42%, for example, it can be 38.5%, 39%, 39.5%, 40%, 40.5%, 41%, 41.5%, 42%, etc., thereby further improving the wettability of the electrolyte to the negative electrode sheet and further improving the liquid retention rate of the negative electrode sheet.
[0042] When the electrode sheet is a positive electrode sheet, the positive electrode sheet includes: a positive electrode current collector and a positive electrode active material layer, the positive electrode active material layer is arranged on at least a portion of the surface of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material, a positive electrode binder and a positive electrode conductive agent. In the embodiments of the present application, the mass ratio of the positive electrode active material, the positive electrode conductive agent and the positive electrode binder in the positive electrode active material layer is not particularly limited, and can be set by those skilled in the art according to actual needs.
[0043] In the embodiment of the present application, the positive electrode current collector may be made of a material with good electrical conductivity and mechanical strength, such as aluminum foil.
[0044] In the embodiments of the present application, the specific types of positive electrode active materials are not particularly limited, and those skilled in the art can select them according to actual needs. As some specific examples, the positive electrode active materials include at least one of lithium iron phosphate, ternary lithium, lithium cobalt oxide, lithium manganese oxide, lithium nickel-rich lithium manganese oxide and lithium iron manganese phosphate.
[0045] In the embodiments of the present application, the specific type of the positive electrode conductive agent is not particularly limited, and those skilled in the art can select it according to actual needs. As some specific examples, the positive electrode conductive agent includes at least one of carbon black, acetylene black, Ketjen black, graphene, and carbon nanotubes. Similarly, the specific type of the positive electrode binder is not particularly limited, and those skilled in the art can select it according to actual needs. As some specific examples, the positive electrode binder includes at least one of polymers such as polyacrylic acid, polyimide, and polyvinylidene fluoride and their derivatives.
[0046] When the electrode sheet is a negative electrode sheet, the negative electrode sheet includes: a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer is arranged on at least part of the surface of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material, a negative electrode binder and a negative electrode conductive agent. In the embodiments of the present application, the mass ratio of the negative electrode active material, the negative electrode conductive agent and the negative electrode binder in the negative electrode active material layer is not particularly limited, and can be set by those skilled in the art according to actual needs.
[0047] In the embodiment of the present application, the negative electrode current collector may be made of a material with good electrical conductivity and mechanical strength, such as copper foil.
[0048] In the embodiments of the present application, the specific types of negative electrode active materials are not particularly limited, and those skilled in the art can select them according to actual needs. As some specific examples, the negative electrode active materials include at least one of graphite, mesophase microcarbon beads (abbreviated as MCMB), hard carbon and soft carbon.
[0049] In the embodiments of the present application, the specific type of the negative electrode conductive agent is not particularly limited, and those skilled in the art can select it according to actual needs. As some specific examples, the negative electrode conductive agent includes at least one of carbon black, acetylene black, Ketjen black, graphene, and carbon nanotubes.
[0050] Similarly, the specific type of the negative electrode binder is not particularly limited, and those skilled in the art can select it according to actual needs. As some specific examples, the negative electrode binder includes at least one of polyacrylic acid, styrene-butadiene rubber, polytetrafluoroethylene, LA-123 series and other aqueous binders.
[0051] In a second aspect of the present application, the present application proposes a method for preparing a pole piece. According to an embodiment of the present application, the method includes:
[0052] A cellulose ether polymer solution is sprayed on at least a portion of the surface of the active material layer away from the current collector, and dried to obtain a pole piece.
[0053] According to some specific embodiments of the present application, a cellulose ether polymer solution is sprayed in an atomized manner on at least a portion of the surface of the active material layer away from the current collector, and dried to obtain an electrode. The present application uses an atomized spraying method to spray the cellulose ether polymer solution into the coated electrode. After drying, the cellulose ether polymer solution evaporates, the cellulose ether polymer matrix shrinks, and pores are formed in situ. The method of the present application is simple, and the porosity of the electrode is effectively improved without changing the design of the electrode or damaging the electrode. At the same time, the created pores have the advantages of uniform distribution and good pore structure integrity. The uniform and abundant pores can significantly improve the wettability of the electrolyte. The rapidly shrunk sprayed cellulose ether polymer can also slowly absorb a large amount of electrolyte and gel, which can limit the fluidity of the electrolyte and effectively improve the liquid retention capacity of the electrode.
[0054] Attached Figure 1 A schematic diagram of the process for preparing pole pieces according to some embodiments of the present application, including slurrying (i.e., preparing active material layer slurry), coating (i.e., coating the active material layer slurry on at least a portion of the surface of the current collector), atomizing and spraying the cellulose ether polymer solution, baking and drying, and rolling to obtain pole pieces.
[0055] The technical solution of the present application is applicable not only to positive electrode sheets, but also to negative electrode sheets. First of all, it should be noted that the solvent for forming the slurry of the positive electrode active material layer of the positive electrode sheet is an organic solvent, the solvent for forming the slurry of the negative electrode active material layer of the negative electrode sheet is water, and the solvent for forming the cellulose ether polymer solution is an organic solvent.
[0056] When the technical solution of the present application is used for the positive electrode sheet, refer to the attached Figure 2 In the positive electrode coating process, atomized cellulose ether polymer solution particles are introduced. In the drying process of the positive electrode, the cellulose ether polymer solution has no skeleton support, and the polymer matrix shrinks after the solvent evaporates, thereby obtaining in situ electrode pores with uniform distribution and relatively consistent pore size. The difference from the existing method is that there is no need to change the electrode design and there is no mechanical damage to the electrode. Moreover, after the positive electrode is rolled, the polymer shrinking at the edge of the hole has a certain supporting effect, which protects the integrity of the pore structure to a certain extent. The schematic diagram of the pore formation of the positive electrode is shown in FIG. Figure 2 As shown in the attached Figure 2 In the figure, 201 represents the positive electrode active material layer dressing, 202 represents the positive electrode polymer droplets, 203 represents the polymer layer that shrinks after drying, and 204 represents the pores left after the polymer shrinks.
[0057] The preparation method of the above positive electrode sheet is as follows:
[0058] The positive electrode active material, positive electrode binder and positive electrode conductive agent are put into a stirring tank in proportion and then slurried. The obtained positive electrode slurry is evenly coated on the positive electrode current collector, and then the atomized cellulose ether polymer solution is sprayed on its surface, and then sent to an oven for drying. After the solvent evaporates, the volume of the cellulose ether polymer shrinks, forming an uneven polymer film in the pores, which has a certain supporting effect on the pores. Finally, the prepared positive electrode sheet is rolled according to the same process as the conventional electrode sheet.
[0059] When the technical solution of the present application is used for the negative electrode sheet, refer to the attached Figure 3 Since the solvent for forming the negative electrode active material layer slurry is water, and the solvent for forming the cellulose ether polymer solution is an organic solvent, the cellulose ether polymer dissolved in the organic solvent will undergo a phase transfer process when it meets water. After drying, the cellulose ether polymer particles themselves have a good structural retention effect, the molecular chain is more stretched, and there are more contact sites, which improves the efficiency of electrolyte infiltration. At the same time, the internal wrinkles and pores generated by the cellulose ether polymer swelling when absorbing the electrolyte can absorb and store a large amount of electrolyte, which further improves the infiltration and liquid retention ability of the negative electrode. The schematic diagram of the pore formation of the negative electrode is shown in the figure below. Figure 3 As shown in the attached Figure 3 , 301 represents the negative electrode active material layer dressing, 302 represents the negative electrode polymer droplets, 303 represents the polymer skeleton after phase transfer, 304 represents the polymer particles after drying, 305 represents the polymer skeleton after drying, and 306 represents the finger-like pores.
[0060] In addition, cellulose ether polymer electrolytes consume a small amount of water during the reaction process and initiate reactive grafting on their side chains, which can not only effectively improve the affinity and ion conductivity of the electrolyte, but also act as a moisture absorber to capture the residual moisture in the battery cell and inhibit the side reactions caused by moisture. Synthetic polymers such as polyacrylonitrile do not have this effect.
[0061] The preparation method of the above negative electrode sheet is as follows:
[0062] The negative electrode active material, negative electrode binder and negative electrode conductive agent are put into a stirring tank in proportion and then slurried. The obtained negative electrode slurry is evenly coated on the negative electrode current collector, and then the atomized cellulose ether polymer solution is sprayed on its surface. Phase transfer occurs during the contact of the polymer solution with water, and the polymer matrix also changes from liquid phase to solid phase, and then sent to the oven for drying. After baking, the solvent evaporates, and the polymer skeleton formed by the matrix has good dimensional stability, limited volume shrinkage, and a pore structure dominated by finger-like pores. Finally, the prepared negative electrode sheet is rolled according to the same process as the conventional electrode sheet.
[0063] According to some specific embodiments of the present application, the mass concentration of the cellulose ether polymer solution is 0.5wt% to 15wt%, for example, it can be 0.5wt%, 2wt%, 4wt%, 6wt%, 8wt%, 0wt%, 12wt%, 15wt%, etc. By limiting the mass concentration of the cellulose ether polymer solution within the above range, it can be effectively ensured that a solution with a reasonable viscosity is formed, which can be sprayed on the surface of the electrode by atomization spraying. At the same time, it can be ensured that a certain amount of cellulose ether polymer is contained in the active material layer, thereby further improving the porosity of the electrode, further improving the wettability of the electrolyte to the electrode, and further improving the liquid retention rate of the electrode.
[0064] According to some further specific embodiments of the present application, the viscosity of the cellulose ether polymer solution is 200mPa.s to 1500mPa.s, for example, it can be 200mPa.s, 500mPa.s, 700mPa.s, 1000mPa.s, 1200mPa.s, 1500mPa.s, etc. By limiting the viscosity of the cellulose ether polymer solution within the above range, it can be ensured that the cellulose ether polymer solution is sprayed on the surface of the electrode by atomization spraying, and at the same time, the porosity of the electrode can be further improved, the wettability of the electrolyte to the electrode can be further improved, and the liquid retention rate of the electrode can be further improved.
[0065] In the embodiments of the present application, the solvent in the cellulose ether polymer solution is not particularly limited, and those skilled in the art can select it according to actual needs. As some preferred embodiments, the solvent in the cellulose ether polymer solution includes at least one of N,N-dimethylformamide, N-methylpyrrolidone and dimethyl sulfoxide. The above solvents can effectively dissolve cellulose ether polymers.
[0066] According to some other specific embodiments of the present application, the drying temperature is 60°C to 80°C (for example, it can be 60°C, 65°C, 70°C, 75°C, 80°C, etc.), and the drying time is 6h to 12h (for example, it can be 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc.). Thus, the solvent in the active material layer can be effectively removed, and at the same time, the organic solvent in the cellulose ether polymer solution can be evaporated, the cellulose ether polymer matrix can be contracted, and pores can be formed in situ.
[0067] According to some other specific embodiments of the present application, the dissolution temperature of the cellulose ether polymer solution is 60°C to 100°C, for example, 60°C, 70°C, 80°C, 90°C, 100°C, etc., thereby effectively dissolving the cellulose ether polymer to form a cellulose ether polymer solution.
[0068] According to the method for preparing the pole piece of the embodiment of the present application, a cellulose ether polymer solution is sprayed into the coated pole piece. After drying, the cellulose ether polymer solution evaporates, the cellulose ether polymer matrix shrinks, and pores are formed in situ. The method of the present application is simple, and the porosity of the pole piece is effectively improved without changing the pole piece design or damaging the pole piece. At the same time, the created pores have the advantages of uniform distribution and good pore structure integrity. The uniform and abundant pores can significantly improve the wettability of the electrolyte. The rapidly shrunk sprayed cellulose ether polymer can also slowly absorb a large amount of electrolyte and gel, which can limit the fluidity of the electrolyte and effectively improve the liquid retention capacity of the pole piece. In addition, the cellulose ether polymer in the pole piece will consume a small amount of water when it is soaked in the electrolyte, and initiate a grafting reaction on its side chain, which can not only effectively improve the affinity and ion conductivity of the electrolyte, but also act as a moisture absorbent to capture the residual moisture in the battery cell after baking and inhibit the side reactions caused by moisture.
[0069] In the third aspect of the present application, the present application proposes a battery. According to an embodiment of the present application, the battery has a pole piece of the above embodiment or a pole piece made by the method of the above embodiment. Thus, the high rate performance, energy density, cycle stability and safety of the battery can be effectively improved.
[0070] Specifically, the battery may be a single cell, a battery module, or a battery pack. When the battery is a single cell, the single cell includes a positive electrode sheet, a negative electrode sheet, and a diaphragm, and the diaphragm is disposed between the electrode sheet and the negative electrode sheet. The positive electrode sheet of the single cell adopts the electrode sheet structure of the embodiment of the present application, or the negative electrode sheet of the single cell adopts the electrode sheet structure of the embodiment of the present application, or both the positive electrode sheet and the negative electrode sheet of the single cell adopt the electrode sheet structure of the embodiment of the present application.
[0071] In the fourth aspect of the present application, the present application proposes an electric device. According to an embodiment of the present application, the electric device has a battery as described above, and the battery is used to provide electric energy for the electric device. Therefore, the electric device has all the advantages of the battery, which will not be repeated here.
[0072] Specifically, the electrical equipment may be, but is not limited to, mobile phones, tablets, laptops, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, etc. Electric toys may include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Spacecraft may include airplanes, rockets, space shuttles, and spacecraft, etc.
[0073] The embodiments of the present application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. In addition, unless otherwise explicitly stated, all reagents used in the following embodiments are commercially available or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.
[0074] Example 1
[0075] This embodiment provides a positive electrode sheet, and the preparation method thereof includes:
[0076] (1) Preparation of positive electrode sheet:
[0077] Take the weight average molecular weight M w A quantitative amount of 100000 hydroxypropyl methylcellulose is dissolved in N,N-dimethylformamide at 80°C to prepare a polymer solution with a mass fraction of 5wt%. When the solution viscosity reaches 600mPa.s, an atomizing device is added for standby use.
[0078] (2) Lithium iron phosphate: carbon nanotubes: polyvinylidene fluoride are put into a stirring tank in a mass ratio of 8:1:1 for slurry preparation, the positive electrode slurry is evenly coated on a carbon-coated aluminum foil, and then the above-mentioned atomized polymerization solution is evenly sprayed on the coating, and then sent to an 80°C oven for solvent evaporation for 8 hours to obtain a dried positive electrode sheet, and the positive electrode sheet is roll-pressed to obtain a final positive electrode sheet.
[0079] Example 2
[0080] This embodiment provides a positive electrode sheet. The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0081] Hydroxypropyl methylcellulose is replaced by hydroxyethyl methylcellulose, and its weight average molecular weight M w is 200000.
[0082] Example 3
[0083] This embodiment provides a positive electrode sheet. The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0084] Hydroxypropyl methylcellulose is replaced by hydroxypropyl ethylcellulose, and its weight average molecular weight M w is 20000.
[0085] Example 4
[0086] This embodiment provides a positive electrode sheet. The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0087] Prepare a polymer solution with a mass fraction of 0.5 wt%, and the weight average molecular weight of the polymer is M w When the viscosity of the solution is 200mPa.s, add it to the atomizing device for standby use.
[0088] Example 5
[0089] This embodiment provides a positive electrode sheet. The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0090] Prepare a polymer solution with a mass fraction of 10 wt%, and the weight average molecular weight of the polymer is M w When the viscosity of the solution is 20000 and 500mPa.s, add the atomizing device for standby use.
[0091] Example 6
[0092] This embodiment provides a positive electrode sheet. The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0093] Prepare a polymer solution with a mass fraction of 15 wt%, and the weight average molecular weight of the polymer is M w When the viscosity of the solution is 200000 and the viscosity is 1500mPa.s, add the atomizing device for standby use.
[0094] Example 7
[0095] This embodiment provides a positive electrode sheet. The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0096] The N,N-dimethylformamide in the polymer solution was replaced by N-methylpyrrolidone.
[0097] Example 8
[0098] This embodiment provides a negative electrode sheet, and the preparation method thereof includes:
[0099] (1) Preparation of negative electrode sheet:
[0100] Take the weight average molecular weight M w A quantitative amount of 100000 hydroxypropyl methylcellulose is dissolved in N,N-dimethylformamide at 80°C to prepare a polymer solution with a mass fraction of 5wt%. When the solution viscosity reaches 600mPa.s, an atomizing device is added for standby use.
[0101] (2) Graphite: carbon black: styrene-butadiene rubber are put into a stirring tank in a mass ratio of 8:1:1 for slurry preparation, the negative electrode slurry is evenly coated on the carbon-coated copper foil, and then the above-mentioned atomized polymerization solution is evenly sprayed on the coating, and then sent to an 80°C oven for solvent evaporation for 8 hours to obtain a dried negative electrode sheet, and the negative electrode sheet is roll-pressed to obtain a final negative electrode sheet.
[0102] Example 9
[0103] This embodiment provides a negative electrode sheet. The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0104] Hydroxypropyl methylcellulose is replaced by hydroxyethyl methylcellulose, and its weight average molecular weight M w is 200000.
[0105] Example 10
[0106] This embodiment provides a negative electrode sheet. The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0107] Hydroxypropyl methylcellulose is replaced by hydroxypropyl ethylcellulose, and its weight average molecular weight M w is 20000.
[0108] Embodiment 11
[0109] This embodiment provides a negative electrode sheet. The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0110] Prepare a polymer solution with a mass fraction of 0.5wt%, and the weight average molecular weight of the polymer is M w When the viscosity of the solution is 200mPa.s, add it to the atomizing device for standby use.
[0111] Example 12
[0112] This embodiment provides a negative electrode sheet. The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0113] Prepare a polymer solution with a mass fraction of 10 wt%, and the weight average molecular weight of the polymer is M w When the viscosity of the solution is 20000 and 500mPa.s, add the atomizing device for standby use.
[0114] Embodiment 13
[0115] This embodiment provides a negative electrode sheet. The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0116] Prepare a polymer solution with a mass fraction of 15 wt%, and the weight average molecular weight of the polymer is M w When the viscosity of the solution is 200000 and the viscosity is 1500mPa.s, add the atomizing device for standby use.
[0117] Embodiment 14
[0118] This embodiment provides a negative electrode sheet. The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0119] The N,N-dimethylformamide in the polymer solution was replaced by dimethyl sulfoxide.
[0120] Comparative Example 1
[0121] This comparative example provides a positive electrode sheet, and the preparation method thereof comprises:
[0122] Lithium iron phosphate: carbon nanotube: polyvinylidene fluoride is put into a stirring tank in a mass ratio of 8:1:1 for slurry preparation, the positive electrode slurry is evenly coated on a carbon-coated aluminum foil, and then sent to an 80°C oven for solvent evaporation for 8 hours to obtain a dried positive electrode sheet, which is then roll-pressed to obtain a final positive electrode sheet.
[0123] Comparative Example 2
[0124] This comparative example provides a negative electrode sheet, and the preparation method thereof comprises:
[0125] Graphite: carbon black: styrene-butadiene rubber are put into a stirring tank in a mass ratio of 8:1:1 for slurry preparation, the negative electrode slurry is evenly coated on the carbon-coated copper foil, and then sent to an oven at 80°C for solvent evaporation for 8 hours to obtain a dried negative electrode sheet, which is then roller-pressed to obtain the final negative electrode sheet.
[0126] The mass proportion of the cellulose ether polymer in the electrode sheets prepared in Examples 1 to 14 in the electrode sheet active material layer was tested using the TGA method. The results are shown in Table 1.
[0127] The contact angle, liquid retention rate and porosity of the electrode sheets prepared in Examples 1 to 14 and Comparative Examples 1 to 2 were tested respectively, and the results are shown in Table 1.
[0128] Contact angle test method:
[0129] A contact angle tester is used to test the contact angle between the electrolyte and the electrode after rolling. The smaller the angle, the stronger the wettability of the electrode to the electrolyte.
[0130] The electrolyte includes a solvent and a lithium salt. The solvent is a mixed solvent of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 1:1:1. The lithium salt is LiPF6 with a concentration of 1 mol / L.
[0131] Liquid retention rate test method:
[0132] Take a sample of a 4cm*4cm electrode, weigh the mass m1 before immersion, soak it in the electrolyte for 1 hour, take out the electrode, wipe the free electrolyte on the surface with dust-free paper, weigh the mass m2 after immersion, and calculate the liquid retention rate of the electrode by the formula: (m2-m1) / m1.
[0133] The electrolyte includes a solvent and a lithium salt. The solvent is a mixed solvent of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 1:1:1. The lithium salt is LiPF6 with a concentration of 1 mol / L.
[0134] Porosity test method:
[0135] Take a 4cm*4cm electrode, measure the electrode thickness d, weigh the mass before immersion m3, soak it in n-butanol for 1h, take out the electrode, wipe the free solution on the surface with dust-free paper, weigh the mass after immersion m4, and use the formula: porosity = (m4-m3) / ρV, ρ is the density of n-butanol = 0.8148g / cm 3 , V is the volume of the electrode, calculate the porosity of the electrode.
[0136] Table 1
[0137]
[0138]
[0139] It can be seen from Table 1 that compared with Comparative Example 1, the contact angle of the positive electrode sheets of Examples 1 to 7 is significantly reduced, and the liquid retention rate and porosity of the positive electrode sheets of Examples 1 to 7 are significantly improved. It can be seen that Examples 1 to 7 of the present application use an atomized spraying method to spray the cellulose ether polymer solution onto the coated positive electrode sheet. After drying, the cellulose ether polymer solution evaporates, the cellulose ether polymer matrix shrinks, and pores are formed in situ, thereby effectively improving the liquid retention rate and porosity of the positive electrode sheet, and significantly reducing the contact angle of the positive electrode sheet.
[0140] It can be seen from Table 1 that compared with Comparative Example 2, the contact angle of the negative electrode sheets of Examples 8 to 14 is significantly reduced, and the liquid retention rate and porosity of the negative electrode sheets of Examples 8 to 14 are significantly improved. It can be seen that Examples 8 to 14 of the present application use an atomized spraying method to spray the cellulose ether polymer solution onto the coated negative electrode sheet. After drying, the cellulose ether polymer solution evaporates, the cellulose ether polymer matrix shrinks, and pores are formed in situ, thereby effectively improving the liquid retention rate and porosity of the negative electrode sheet, and significantly reducing the contact angle of the negative electrode sheet.
[0141] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0142] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A pole piece, characterized in that: include: current collector; An active material layer is disposed on at least a portion of the surface of the current collector, and the active material layer includes a cellulose ether polymer, and the cellulose ether polymer is located in the gaps contained in the active material layer.
2. The pole piece according to claim 1, characterized in that: The weight average molecular weight of the cellulose ether polymer is 20,000 to 200,000.
3. The pole piece according to claim 1 or 2, characterized in that: The cellulose ether polymer includes at least one of hydroxypropyl methylcellulose, hydroxyethyl methylcellulose and hydroxypropyl ethylcellulose.
4. The pole piece according to any one of claims 1 to 3, characterized in that: The mass proportion of the cellulose ether polymer in the active material layer is 1% to 5%.
5. The pole piece according to any one of claims 1 to 4, characterized in that: The electrode sheet is a positive electrode sheet, and the porosity of the positive electrode sheet is 36.5% to 40%.
6. The pole piece according to any one of claims 1 to 4, characterized in that: The electrode sheet is a negative electrode sheet, and the porosity of the negative electrode sheet is 38.5% to 42%.
7. A method for preparing the pole piece according to any one of claims 1 to 6, characterized in that: include: A cellulose ether polymer solution is formed on at least a portion of the surface of the active material layer away from the current collector, and dried to obtain a pole piece.
8. The method according to claim 7, characterized in that The mass concentration of the cellulose ether polymer solution is 0.5 wt% to 15 wt%.
9. The method according to claim 7 or 8, characterized in that: The viscosity of the cellulose ether polymer solution is 200mPa.s to 1500mPa.s.
10. The method according to any one of claims 7 to 9, characterized in that: The solvent in the cellulose ether polymer solution includes at least one of N,N-dimethylformamide, N-methylpyrrolidone and dimethyl sulfoxide.
11. The method according to any one of claims 7 to 10, characterized in that: The cellulose ether polymer solution is sprayed on at least a portion of the surface of the active material layer away from the current collector in an atomized manner and dried to obtain a pole piece.
12. A battery, characterized in that: A pole piece according to any one of claims 1 to 6 or a pole piece made by the method according to any one of claims 7 to 11.
13. An electrical equipment, characterized in that: A battery according to claim 12.
Citation Information
Patent Citations
Battery electrode and its manufacturing method
CN102290560A
Battery electrode and manufacturing method thereof, non-aqueous electrolyte battery, battery pack, and active material
CN103210531A
Method for manufacturing electrode sheet
CN106356504A
Lithium ion battery anode material, negative plate of lithium ion battery, preparation method for negative plate and lithium ion battery
CN108258246A
Pole piece and battery
CN112952033A